Kompleksnoe mnogofunkcional'noe ustrojstvo dlja obucenija i trenirovki tjazeloatletov i pauerlifterov - Volkov, N. P. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The author has created the multifunctional device for teaching and training of weightlifters and powerlifters including four blocks: foot block, loading, the block of installation and task of moving of a sports bar and the block of accommodation of the athlete.